ETR 300 : Fastpack Enterprise / Yitzhak Baharom... [et al.] - Baharom, Yitzhak; Mohd Johar, Mohd Amir; Abdul Rahim, Hanif; Md Rozali, Noorazwandi; Harun, Mohd Saiful (2001)
Fastpack Enterprise is the company that produce various of boxes for business user as well as the individual user. the name of fastpack is consist of the element of fast and yet easy to use. The choose of this product is because the demand for the boxes is high especially in field of food industry, product and material manufacturing. The company is located at Bukit Makmur Light industrial park, sungai petani, Kedah.